Lithium‐Ion Batteries: An Antiaging Electrolyte Additive for High‐Energy‐Density Lithium‐Ion Batteries (Adv. Energy Mater. 20/2020). Issue 20 (26th May 2020) - Han, Jung‐Gu; Hwang, Chihyun; Kim, Su Hwan; Park, Chanhyun; Kim, Jonghak; Jung, Gwan Yeong; Baek, Kyungeun; Chae, Sujong; Kang, Seok Ju; Cho, Jaephil; Kwak, Sang Kyu; Song, Hyun‐Kon; et al.
Abstract : In article number 2000563, Sang Kyu Kwak, Hyun‐Kon Song, Nam‐Soon Choi, and co‐workers show that the antioxidant activity of MA‐C60 inhibits the unfavourable reaction between electrolyte solvents and superoxide radicals generated from Li‐rich cathodes, and that MA‐C60 traps water molecules via hydrogen bonding or ionic interactions, leading to the suppression of the undesirable hydrolysis reactions of LiPF6 .